Dual mobility total hip arthroplasty in the treatment of femoral neck fractures: systematic review and meta-analysis. (1st November 2020) - Cha, Yong-Han; Yoo, Jun-Il; Kim, Jung-Taek; Park, Chan-Ho; Ahn, Young-Sun; Choy, Won-Sik; Ha, Yong-Chan; Koo, Kyung-Hoi
Abstract : Aims: To evaluate the rate of dislocation following dual mobility total hip arthroplasty (DM-THA) in patients with displaced femoral neck fractures, and to compare rates of dislocation, surgical-site infection, reoperation, and one-year mortality between DM-THA and bipolar hemiarthroplasty (BHA). Methods: Studies were selected based on the following criteria: 1) study design (retrospective cohort studies, prospective cohort studies, retrospective comparative studies, prospective comparative studies, and randomized controlled studies (RCTs)); 2) study population (patients with femoral neck fracture); 3) intervention (DM-THA or BHA); and 4) outcomes (complications during postoperative follow-up and clinical results). Pooled meta-analysis was carried out to evaluate the dislocation rate after DM-THA and to compare outcomes between DM-THA and BHA. Results: A total of 17 studies (ten cohort studies on DM-THA and seven comparative studies of DM-THA and BHA) were selected. These studies included 2, 793 patients (2, 799 hips), made up of 2, 263 DM-THA patients (2, 269 hips) and 530 BHA patients (530 hips). In all, 16 studies were analyzed to evaluate dislocation rate after DM-THA. The cumulative dislocation rate was 4% (95% confidence interval (CI) 3 to 5). Seven studies were analyzed to compare the rates dislocation and surgical-site infection. The rate of dislocation was significantly lower in the DM-THA group than in the BHA group (risk ratio (RR) 0.3; 95% CI 0.17 to 0.53, p < 0.001, Z −4.11). There was no significant difference in the rate of surgical-site infection between the two groups (p = 0.580). Six studies reported all-cause reoperations. The rate of reoperation was significantly lower in the DM-THA group than in the BHA group (RR 0.5; 95% CI 0.32 to 0.78, p = 0.003, Z −3.01). Five studies reported one-year mortality. The mortality rate was significantly lower in the DM-THA group than in the BHA group (RR 0.58 95% CI 0.45 to 0.75, p < 0.0001, Z −4.2). Conclusion: While the evidence available consisted mainly of non-randomized studies, DM-THA appeared to be a viable option for patients with displaced fractures of the femoral neck, with better reported rates of dislocation, reoperation, and mortality than BHA.